Polyhydroxyalkanoates (PHAs) production from fermented cheese whey by using a mixed microbial culture. (October 2016) - Colombo, Bianca; Pepè Sciarria, Tommy; Reis, Maria; Scaglia, Barbara; Adani, Fabrizio
Highlights: Fermented cheese whey (CW) were used as substrate for PHA production. Enriched mixed microbial culture was produced from activated sewage sludge. Different organic acids configuration of fermented CWs modified PHA composition. PHA yield obtained were of 60–70 g kgcheese  whey  Total Solid −1 . Abstract: Two fermented cheese wheys (FCW), FCW1 composed of lactic, acetic and butyric acids in the proportion of 58/16/26 (% CODOrganic Acid (OA) ) and FCW2 composed of acetic, propionic, butyric, lactic and valeric acids in the proportion of 58/19/13/6/4 (% CODOA ) were used to produce polyhydroxyalkanoates (PHAs) by using a pre-selected mixed microbial culture (MMC). PHA accumulation gave for fermented FCW1 a PHA yield (Ytot ) of 0.24 ± 0.02 mg CODPHA  mg CODSoluble  Substrate(SS) −1 and a total PHA production, referred to the substrate used, of 60 g PHA kgcheese  whey  Total Solids (TS) −1 . For fermented FCW2 results were: PHA yield (Ytot ) of 0.42 ± 0.03 mg CODPHA  mg CODSS −1 and PHA from a substrate of 70 g PHA kgcheese  whey  TS −1 . Qualitatively, PHAs from FCW1 was made up exclusively of 3-hydroxybutyrate (HB), while those obtained from FCW2 were composed of 40% of 3-hydroxyvalerate (HV) and 60% of HB.